Pitting Corrosion in AISI 304 Rolled Stainless Steel Welding at Different Deformation Levels - Francisco-Javier Cárcel-Carrasco; Manuel Pascual-Guillamón; Lorenzo Solano García; Fidel Salas Vicente; Miguel-Angel Pérez-Puig (Applied Sciences, 2019)
This paper analyzes pitting corrosion at the weld zone and at the heat affected zone (HAZ) in AISI 304 rolled stainless steel welds. As the aforementioned material is one of the most frequently used types of stainless steel, it is needful to be aware of the mechanisms that lead to its deterioration, like corrosion, since it can cause failures or malfunction in a wide variety of products and facilities. For the experimental tests 1.5 mm thick AISI 304 stainless steel plates were welded and rolled to different thicknesses and after, the samples were subjected to mechanical and corrosion tests and to a micrograph study. Deformation stresses and other intrinsic metallurgic and physic-chemical transformations that occur during cold rolling and welding, and that are key factors in the anti-corrosion behavior of AISI 304 rolled stainless steel, have been observed and analyzed. A correlation has been found between cold work levels in test samples and number of pits after corrosion tests.